Performance Characterization of 450 nm Visible Light Based Photoacoustic Imaging for Phantom Imaging of Synthetic Dye Contrast Agents - Mahendra Kusuma Nugraha; Moh. Ali Joko Wasono; Mitrayana Mitrayana (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2022)
Performance characterization of 450 nm visible light photoacoustic imaging has been carried out through phantom imaging of methylene blue (MB), methyl orange (MO), and methyl red (MR) dye solutions. The phantom was made of a nylon tube with a diameter of 5.0 mm (outside) and 4.6 mm (inside) having a height of 2.0 mm along with a 6×6 cm black galvanized aluminum plate as the background medium. The nylon tube was filled with each type of solution with varying molecular concentrations of 10, 25, 50 and 100 ppm. Twelve (12) phantom objects were imaged in an area of 10×10 cm. The visible absorption peak known from UV-Visible spectroscopy for each type of solution is at 664 nm (methylene blue), 465 nm (methyl orange), and 522 nm (methyl red). It was also known that the amplitude of PA emissions would increase proportionally to the concentration of dye molecules. Overall, methyl orange solutions had the highest photoacoustic emission amplitude distribution. The analysis showed that the ratio of inner diameter (ID) and wall thickness (WT) between the MB and MO phantom images to the original object were 1:0.83 and 1:0.74 (ID) and 1:3 and 1:1.5 (WT), respectively. On the other hand, the ratio of the outer diameter (OD) of the MR phantom image to the original object is 1:1.28.